Contemporary Oil Painting Art and Art Market in Real Life - Liu, Qisheng (Transactions on Social Science, Education and Humanities Research, 2024)
Since the reform and opening up in the 1980s, in the context of cultural exchange between China and the West, Chinese culture, art, and ideological concepts have undergone tremendous changes. Under the influence of Western painting, the development of oil painting art has further explored and studied modernist painting. At the same time, under the influence of Western modernist painting art, Chinese oil painting art has also shown a phenomenon of a hundred flowers blooming, such as the diversification of artistic styles and the diversification of painting language types, thereby creating the birth of various new painting schools. In the context of globalized art and culture, contemporary Chinese oil painting has also begun to go global. However, the development of contemporary Chinese oil painting is still criticized by the art of easel painting and photorealistic painting. Faced with the booming art market and the diversification of evaluation standards, how to understand the current situation and trends of contemporary oil painting art development is a question worthy of our in-depth research and reflection.